Electrode Modified with a Polymer of Aniline and 3-Hexylthiophene to Be Assayed in the Selective Determination of Nitrate - Gacitua-Santalices, M; Gacitua-Santalices, M (Sociedad Chilena de Quimica, 2020)
In this work, platinum electrodes are modified with poly[4-(3-hexyl-2-thiophene)-aniline], PTANIr2, and characterized by cyclic voltammetry. In the presence of nitrate in the electrolytic medium, an oxidation signal at 0.6 V vs. SCE is recorded, so the response of this modified electrode, Pt|PTANIr2, is evaluated to determine its relationship with the concentration of the anion. Thus, it is verified that the best response is achieved by chrono-amperometry, obtaining a directly proportional relationship between the charge and the concentration, in an interval between 5 and 100 mg L-1of the anion, with r2= 0.996. Furthermore, it is found that the response of Pt|PTANIr2 is quite selective for nitrate, since there is no response for anions such as HPO4-, PO42-, ClO4-, F-, Cl-, Br-, I-, and NO2-, thereby contributing significantly to solving the main problem of devices of this type proposed so far. Finally, the surfaces were characterized by atomic force microscopy, showing a strong anionpolymer layer interaction. Thus, this material can be proposed to be tested as a columbimetric nitrate sensor, highlighting the possibility of varying the area of the electrode and/or the thickness of the deposited polymeric layer and with it, the sensitivity of the device. © 2020 Sociedad Chilena de Quimica. All rights reserved.